“Here is the house”: A reading of the house(s) in The bluest eye, by Toni Morrison - Araújo, Eliza de Souza Silva; e Silva, Danielle de Luna (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2020)
In the present article we propose a reading of space in The bluest eye, by Toni Morrison, as a motif for plot and character development. The narrative takes place in Lorraine, Ohio, also hometown to Morrison. Other biographical elements appear in the narrative, the spatial being of utmost importance to this study. We explore the novel’s houses as spatial elements that add to characters’ subjectivities and embed the underlying theme of class. The narrative, which tells not only the story of Pecola, the protagonist, but gives us a detailed account of the lives of her mother, father, host family and community, starts with a simple description of a house as a place where a family lives and where everything comes together in harmony. This is done through the presentation of a primer which depicts language used in Dick and Jane books, texts historically used to initiate kids in reading. Such reference also implicates the representation of a perfect white suburban family where everyone gets along. Houses, furniture, backyards and other home-related elements foreshadow the unfortunate events to unravel in Pecola’s life along the novel. In terms of their significance in a broader perspective, we grasp that houses are in the novel also to set and depict the families’ background and current conditions in terms of class. Not only do houses help reinforce character traits, they stand as a social criticism to the economic conditions of blacks, also determined by whether their skin is darker or has a lighter shade. ——————————————————————————————- “AQUI ESTÁ A CASA”: UMA LEITURA DA(S) CASA(S) EM THE BLUEST EYE, DE TONI MORRISON No presente artigo, propomos uma leitura do espaço em The bluest eye, de Toni Morrison, como um mote para o desenvolvimento das personagens. A narrativa se desenrola em Lorraine, Ohio, também cidade onde Morrison nasceu. Outros elementos biográficos aparecem na narrativa, o espaço sendo o de maior importância nesse estudo. Exploramos as casas do romance que adicionam à subjetividade das personagens e estão implicadas no tema de classe. A narrativa, que nos conta a história de Pecola, a protagonista, mas também nos dá um apanhado detalhado das vidas de sua mãe, pai, família acolhedora e comunidade, começa com uma simples descrição de uma casa como o lugar em que uma família vive e tudo se encontra em harmonia. Isso é feito através da apresentação de um primer que apresenta linguagem usada nos livros de Dick and Jane, textos historicamente usados para iniciar crianças na leitura. Tal referência também implica a representação de uma família branca e suburbana perfeita, na qual todos se entendem. Casas, mobília, quintais e outros elementos ligados à moradia prenunciam os eventos trágicos prestes a se desenrolar na vida de Pecola ao longo da narrativa. Em termos de sua significância numa perspectiva mais abrangente, entendemos que as casas estão no romance para determinar as origens sociais das famílias e suas condições presentes em termos de classe. Não só as casas reforçam características das personagens, elas também posicionam uma crítica social à condição financeira da população negra, também determinada pelo tom mais escuro ou mais claro de sua pele. — Original em inglês.